How Fletcher was hatched - Devlin, Wende; Devlin, Harry, 1918- (New York, Parents' Magazine Press, 1969)
Feeling his mistress has rejected him in preference to her newly hatched chicks, the old hound dog decides he must hatch from an egg and learn to say "peep" to regain favor.
Keywords: Dogs -- Fiction